Roots of Collaborative Inquiry and Generative Dialogue for Educational Leadership (Alberta Journal of Educational Research, 2021)
The twin processes of collaborative inquiry and generative dialogue underpin two closely aligned and increasingly influential school leadership development programs, one in Alberta, Canada, and the other in New South Wales, Australia. This paper focuses primarily on the Australian program, the character of which has been strongly influenced by its Canadian predecessor. Of interest in the paper is the nature of the foundations of collaborative inquiry and generative dialogue, and the relationship of these processes to an expressed need for better leadership development in the Australian school sector. David Townsend and Pam Adams, who are principally responsible for generating a school leadership development model based on the use of both collaborative inquiry and generative dialogue, have sought to show how these two processes should function seamlessly, but there is more to be said about the nature of their relationship. This paper seeks to throw more light on the integral role played by generative dialogue in empowering collaborative inquiry in the context of school leadership development.Keywords: generative dialogue, collaborative inquiry, school leadership, leadership development, educational leadership programsLes processus jumeaux de l'enquête collaborative et du dialogue génératif sous-tendent deux programmes de développement du leadership scolaire étroitement alignés et de plus en plus influents, l'un en Alberta, au Canada, et l'autre en Nouvelle-Galles du Sud, en Australie. Cet article se concentre principalement sur le programme australien, dont le caractère a été fortement influencé par son prédécesseur canadien. Il s'intéresse à la nature des fondements de l'enquête collaborative et du dialogue génératif, ainsi qu'à la relation entre ces processus et le besoin exprimé d'un meilleur développement du leadership dans le secteur scolaire australien. David Townsend et Pam Adams, qui sont les principaux responsables de la création d'un modèle de développement du leadership scolaire basé sur l'utilisation de l'enquête collaborative et du dialogue génératif, ont cherché à montrer comment ces deux processus devraient fonctionner de manière transparente, mais il y a plus à dire sur la nature de leur relation. Cet article vise à mettre en lumière le rôle intégral joué par le dialogue génératif dans l'autonomisation de l'enquête collaborative dans le contexte du développement du leadership scolaire.Mots clés : dialogue génératif, enquête collaborative, leadership scolaire, développement du leadership, programmes de leadership scolaire